Women in Late Antiquity and Early Christianity: The Voices and Deeds of the “Silent” Minority (Annual of the Faculty of Philosophy in Skopje, 2018)
The status of women in Late Antiquity and early Christianity has been an inspiringtheme for debate in the last few decades. The New Testament is full of texts that testifyabout the involvement of women in early Christian communities. In the Epistles of St.Paul, he salutes women, addresses them as collaborators, one of them as the deaconess, andeven calls one the Apostle. This text makes a brief overview of the role and position of womenin antiquity, which, in addition to the later analysis of their place in the early Christianworld, will best show whether and how much the new religion influenced their, to usehere an exquisite modern word, emancipation. In the context of this, we are also going tostudy several examples of deciduous mosaics from archaeological sites in the Republic ofMacedonia.
Keywords: WOMEN; LATE ANTIQUE; EARLY CHRISTIANITY; MOSAIC DESCENDANTS